Rosalind Fredericks, Garbage Citizenship: Vital Infrastructures of Labor in Dakar, Senegal - Myers, Garth (Journal for the Study of Religion, Nature and Culture, 2021)
Rosalind Fredericks, Garbage Citizenship: Vital Infrastructures of Labor in Dakar, Senegal (Durham and London: Duke University Press, 2018) xi+200 pp., 23.95 (pbk), ISBN: 978-1-4780-0141-6.